PENGARUH DIGITAL MARKETING DAN BRAND IMAGE TERHADAP MINAT NASABAH DALAM PENGGUNAAN PRODUK PADA BANK SYARIAH INDONESIA KCP SALATIGA: THE INFLUENCE OF DIGITAL MARKETING AND BRAND IMAGE ON CUSTOMER INTEREST IN PRODUCT USAGE AT BANK SYARIAH INDONESIA, SALATIGA SUB-BRANCH OFFICE - Ofita Fitriyani; Qi Mangku Bahjatullah; Akhmad Trisna Wijaya (Universitas Wahid Hasyim Semarang, 2026)
This study aimed to examine the significant effect of digital marketing and brand image on customer interest in using products at Bank Syariah Indonesia (BSI) KCP Salatiga. The banking industry needed to adapt to rapid technological advancements and strengthen its brand image to attract and retain customers effectively. This research used a quantitative approach combined with a field study method to gather empirical data. The sample consisted of 100 respondents who were selected through a purposive sampling technique based on the Cochran formula calculations. Primary data were collected using a Likert scale questionnaire and subsequently analyzed using specific instrument tests, classical assumption tests, and hypothesis testing including T-test, F-test, and Coefficient of Determination through SPSS version 26. The findings showed that digital marketing partially did not have a significant effect on customer interest. Conversely, brand image partially demonstrated a positive and significant effect on customer interest. Simultaneously, both digital marketing and brand image significantly affected customer interest, contributing 66% to the variance. The study concluded that building a strong brand image was the primary driver of customer interest.